Electrodeposited Co-Mn-Sn multicomponent alloy as an efficient electrocatalyst for hydrogen evolution reaction - Chandran, M. Athira; Karumuthil, Subash Cherumannil; Singh, Ashutosh K.; Prasad, Bhagavatula L. V. (International Journal of Hydrogen Energy, 2024)
Despite having exciting material characteristics, the potential of multi-component alloys (MCAs) as electrocatalysts has not been fully realized. In this work, efficient binary and ternary MCA electrocatalysts containing inexpensive metals like Co, Mn and Sn have been prepared via the electrodeposition process. When tested for hydrogen evolution reaction (HER) in an alkaline medium, ternary Co-Mn-Sn alloy displayed enhanced activity with the lowest overpotential of 136 mV, a Tafel slope of 111 mV dec 1 and a very low charge transfer resistance, making it superior to the binary alloys (Co-Mn and Co-Sn), or the single metal catalysts (Co, Mn and Sn). The ternary alloy also displayed high electro-chemical and structural stability, making it a viable electrocatalyst for the hydrogen economy.(c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Clean energy; electrocatalysis; Electrodeposition; hydrogen evolution reaction; Multi-component alloy; Non-platinum group metals

Polymer nanocomposites with UiO-derived zirconia fillers for energy generation and pressure-sensing devices: the role of crystal structure and surface characteristics - Mukherjee, Gargi; Verma, Ankur; Madhu, Arjun Hari; Prasad, Bhagavatula L. V.; Karumuthil, Subash Cherumannil (ACS Applied Nano Materials, 2024)
Piezoelectric energy harvesting and pressure sensing using polymer nanocomposites have opened up promising avenues in the field of flexible electronics. Herein, the influence of varying crystal structures of zirconia nanoparticles on a piezoelectric energy-generating zirconia-poly(vinylidene difluoride) (PVDF) composite is investigated, and the fabrication of a security alert pavement unit using the material with an optimized composition is demonstrated. More specifically, two metal-organic frameworks, UiO-66 and UiO-67, were employed to synthesize four different types of zirconia nanoparticles with precise control of the monoclinic and tetragonal phases. Polymer nanocomposite with monoclinic zirconia nanoparticles derived from UiO-66 (ZrO2-66m) performed better than other derivatives with 61% enhancement in the beta phase with respect to pure PVDF. It was hypothesized that the stable crystalline structure of the monoclinic phase might act as a better nucleating agent, and among monoclinic derivatives, ZrO2-66m was found to be more hydrophobic, probably enabling a better interaction with PVDF. Subsequently, a prototype device with a PVDF-ZrO2-66m (P/66m) film was made and tested for its energy generation. The maximum output voltage generated by the device under an irregular biomechanical hand tapping force of 8-9 N was 80 V, while the maximum open circuit current was found to be 65 mu A. The prototype displayed a power of 2162.24 mu W at a load resistance of 1 M Omega. A laboratory scale demonstration was executed with the prototype as an energy-generating and security alert pavement unit. A wireless, Bluetooth-based security alert system supported by an Android application was developed and demonstrated as a promising application with the fabricated prototype. The results and demonstrations validate that the PVDF-monoclinic ZrO2 nanoparticle nanocomposites will be an excellent value addition for flexible, durable energy generation and pressure-sensing applications.
Keywords: energy generation and pressure sensing; piezoelectric materials; PVDF/ZrO2 polymernanocomposite; self-powered devices; wearable electronics

Tailoring of rheological properties through hydrophobic interactions in silica-based liquid crystal gels - Sumana, S.; Chakrabortty, Pratyasha; Karumuthil, Subash Cherumannil; Prasad, S. Krishna; Prasad, Bhagavatula L. V. (ChemPhysChem, 2025)
Modification of the intrinsic hydrophilic character of the pristine silica nanoparticles (SiNP) decorated with silanol moieties into a hydrophobic state has been of substantial interest, owing to the amenability to gelation of desirable liquids. Many reports exist on composites of SiNP with liquid crystals (LCs), an epitome of anisotropic soft matter. The fumed SiNP, unlike its precipitated counterpart, has been the preferred variety. A family of colloidal gel systems is reported, consisting of precipitated SiNP in a nematic LC, formed by substituting some native silanols with methyl, butyl, or dodecane chains. Detailed steady state and oscillatory rheological measurements are performed, along with analyses using the soft glass and other viscoelastic models. The study demonstrates that the sophisticated modified fractional models, Kelvin-Voight and Maxwell, proposed for generalized viscoelastic behavior of soft materials, are quite successful in describing these nematic gels as well. The observed nontrivial relationship between the ligand length and the strength of the gel network is elucidated on the basis of a judicious combination of the van der Waals, hydrogen bonding, and hydrophobic interactions, leading to a detailed understanding of the viscoelastic behavior of the composites and the influence of SiNP surface chemistry.
Keywords: fractional viscoelastic models; Hydrophobic; nematic; rheological studies; silica nanoparticles